Find thevalue of pynomial 2x-3x^2+1 p(x)=-2
Answers
Answered by
0
Answer:
- 15
Step-by-step explanation:
2x-3x^2+1 ( putting x=-2)
2(-2) - 3(-2)^2+1
= - 4-12+1=-15
Hope it will help you
Thank you....
Answered by
0
Answer:
Step-by-step explanation: hello my friend,,, it's easy to understand.
Follow the instructions
p(x)=-2 [given]
p(x)= 2x-3x^2+1
p(x)= 2(-2)-3(-2)^2+1
p(x)= -4-12+1
p(x)= -16+1
p(x)= -15
IT IS VERY SIMPLE AS SIMPLE OKAY.......
THANKS BRO/SIS
MYSELF SASHMIT TRIPATHY
Similar questions